Challenging poststructuralist character analysis: A systematic review supporting archetypal depth over surface complexity - Muhammad Daffa Syafiq Nashr Ad-Diba’i (Priviet Social Sciences Journal, 2026)
This systematic literature review examines Jack Horner's characterization in "Puss in Boots: The Last Wish" as a paradigmatic critique of poststructuralist shallow-depth approaches to character analysis. Drawing on mass psychology theory, archetypal analysis, and Individual Psychology frameworks, this study challenges the dominant poststructuralist emphasis on interpretive complexity and semantic instability in contemporary character studies. Using a systematic review methodology, this research analyzes 33 high-quality studies across interdisciplinary domains, including character analysis, poststructuralist theory, mass psychology, and audience response research. The data sources included peer-reviewed articles, theoretical works, and empirical studies examining the effectiveness of character construction and cultural transmission mechanisms. The results demonstrate that Jack Horner's pure evil characterization achieves superior psychological resonance and collective engagement through archetypal depth rather than poststructuralist surface complexity. The physiological evidence of audience synchrony, cross-cultural validation of archetypal patterns, and pedagogical effectiveness in moral instruction consistently support depth approaches over interpretive multiplicity. This study contributes to cultural psychology and media studies by revealing how universal psychological patterns transcend poststructuralist limitations while maintaining practical applicability across diverse contexts. The findings indicate that archetypal character construction serves essential functions in collective meaning-making, moral development, and cultural transmission that poststructuralist deconstruction actively undermines, with significant implications for media production, educational policy, and contemporary approaches to character analysis in academic and cultural contexts.